A Girl Named Carla - Luca Paci (2006)
La ragazza Carla is a long prose-poem written between 1954 and 1957 set in Milan just after the Second World War. The protagonist is seventeen-year-old Carla Ambrogio who works as a 'shorthand typist in the shadow of the Duomo'. Pagliarani describes how Carla confronts the hostile environment in which she lives and works with courage and intelligence. We can see the opening scene as a 'pan' of Milan with its traffic, people, railway bridges, and lorries. The city still bears the scars of war-time bombings and many buildings are still gutted. However, there are already signs of the forthcoming economic boom such as neon lights, cinemas and shopping centres. The young woman will gradually learn how to cope with life and will become part of the anonymous flow of the city like everyone else. Soon she will forget her fear of living and grow up accepting the norms and conventions of the society she lives.